Strategy for Beef Cattle Agribusiness Development in North Sulawesi - Jolyanis Lainawa; Paulus Kindangen; Tri Oldi Rotinsulu; J.F. Alfa Tumbuan (International Journal of Applied Business and International Management, 2019)
The business of raising cattle in North Sulawesi is still carried out in traditionalextensive ways, because the main objective of farmers is to raise cattle only to be used as agricultural labor. As a result, the population and productivity of cattle in North Sulawesi are not well developed. Though the number of requests for beef consumption is very high, so that there is a gap between consumption needs and the availability of production. For the development of the agribusiness system, the concept of development strategy is needed, so the purpose of this study is to find a model for agribusiness development of beef cattle in North Sulawesi. The research method used is qualitative with a case study design. Data analysis is "four qualitative stages" and "strategy formulations" (EFE, IFE, SWOT, IE and QSPM). Based on the results of analysis, beef cattle farms in North Sulawesi are in a growing and constructive position which has a high industrial attractiveness and has the potential to be developed towards a modern-intensive maintenance system, namely developing business with agribusiness system models (efficiency and market considerations) and farming systems / family system (consideration of traditional experience and quantity of available farmer resources).